STRATEGI GURU MENGGUNAKAN MODEL MIND MAPPING UNTUK MENGATASI KESULITAN MENULIS PADA SISWA SEKOLAH DASAR - Nur Hendra Subekti; Ahmad Nurefendi Fradana (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
This study aims to describe teachers’ strategies in using the Mind Mapping model to address writing difficulties among second-grade elementary school students, employing a descriptive qualitative approach conducted at SD Negeri Waung, Krembung Subdistrict, Sidoarjo Regency, with one teacher and six students as research subjects. Data collection was conducted through observation, interviews, and documentation, and analyzed through the stages of data reduction, data presentation, and conclusion drawing using triangulation techniques to ensure data validity. The results of the study indicate that students experience difficulties in starting their writing, developing ideas, and constructing sentences in a coherent manner, However, after implementing mind mapping, there was a noticeable improvement in writing skills, as evidenced by more focused ideas, more coherent sentence structure, and increased student confidence in writing. It can therefore be concluded that the use of mind mapping helps students organize their ideas before putting them into writing; consequently, teachers are encouraged to continue using this method in writing instruction. However, after implementing Mind Mapping, an improvement in writing skills was observed, characterized by more focused ideas, more coherent sentence structure, and increased student confidence in writing. It can therefore be concluded that the use of Mind Mapping helps students organize their ideas before putting them into writing; consequently, teachers are advised to utilize this model consistently in writing instruction. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan strategi guru dalam menggunakan model Mind Mapping untuk mengatasi kesulitan menulis pada siswa kelas II sekolah dasar dengan pendekatan kualitatif deskriptif yang dilaksanakan di SD Negeri Waung, Kecamatan Krembung, Kabupaten Sidoarjo, dengan subjek penelitian satu orang guru dan enam siswa, pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi, serta dianalisis melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan dengan teknik triangulasi untuk menjamin keabsahan data, hasil penelitian menunjukkan bahwa siswa mengalami kesulitan dalam memulai tulisan, mengembangkan ide, dan menyusun kalimat secara runtut, namun setelah penerapan Mind Mapping terlihat adanya peningkatan kemampuan menulis yang ditandai dengan ide yang lebih terarah, susunan kalimat yang lebih runtut, serta meningkatnya kepercayaan diri siswa dalam menulis, sehingga dapat disimpulkan bahwa penggunaan Mind Mapping mampu membantu siswa dalam mengorganisasi gagasan sebelum dituangkan ke dalam tulisan, oleh karena itu guru disarankan untuk memanfaatkan model ini secara berkelanjutan dalam pembelajaran menulis.